Continuous Electrical Monitoring in Patients with Arrhythmic Myocarditis: Insights from a Referral Center - Giovanni Peretto (MDPI AG, 2021)
Background. The incidence and burden of arrhythmias in myocarditis are under-reported. Objective. We aimed to assess the diagnostic yield and clinical impact of continuous arrhythmia monitoring (CAM) in patients with arrhythmic myocarditis. Methods. We enrolled consecutive adult patients (n = 104; 71% males, age 47 ± 11 year, mean LVEF 50 ± 13%) with biopsy-proven active myocarditis and de novo ventricular arrhythmias (VAs). All patients underwent prospective monitoring by both sequential 24-h Holter ECGs and CAM, including either ICD (n = 62; 60%) or loop recorder (n = 42; 40%). Results. By 3.7 ± 1.6 year follow up, 45 patients (43%) had VT, 67 (64%) NSVT and 102 (98%) premature ventricular complexes (PVC). As compared to the Holter ECG (average 9.5 exams per patient), CAM identified more patients with VA (VT: 45 vs. 4; NSVT: 64 vs. 45; both p < 0.001), more VA episodes (VT: 100 vs. 4%; NSVT: 91 vs. 12%) and earlier NSVT timing (median 6 vs. 24 months, p < 0.001). The extensive ICD implantation strategy was proven beneficial in 80% of the population. Histological signs of chronically active myocarditis (n = 73, 70%) and anteroseptal late gadolinium enhancement (n = 26, 25%) were significantly associated with the occurrence of VTs during follow up, even in the primary prevention subgroup. Conclusion. In patients with arrhythmic myocarditis, CAM allowed accurate arrhythmia detection and showed a considerable clinical impact.